2021
DOI: 10.1111/jcpe.13433
|View full text |Cite
|
Sign up to set email alerts
|

Healing of buccal gingival recessions following treatment with coronally advanced flap alone or combined with a cross‐linked hyaluronic acid gel. An experimental study in dogs

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 38 publications
(65 reference statements)
5
22
0
Order By: Relevance
“…The histomorphometric assessments revealed that xHyA-treated intraosseous and furcation sites formed significantly greater areas of new cementum and periodontal ligament fibers on previously exposed root surfaces. Similar observations were made from the same treatment sequence applied in gingival recessions [ 39 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 72%
“…The histomorphometric assessments revealed that xHyA-treated intraosseous and furcation sites formed significantly greater areas of new cementum and periodontal ligament fibers on previously exposed root surfaces. Similar observations were made from the same treatment sequence applied in gingival recessions [ 39 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 72%
“…In agreement with the present results, a recent study conducted on dogs by Shirakata et al in 2021 concluded that HA in conjunction with CAF enhances periodontal regeneration and wound healing in gingival recession defects. The CAF/HA group showed a statistically significant reduction in the width of gingival recession (p < 0.01) and a significantly higher formation of connective tissue attachment in the CAF/HA group compared with the CAF group [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, LD-CBCT could be used to monitor whether, and to what extent, bony regeneration occurs after recession coverage. Until now, this could only be determined by means of histological examinations and nonionizing ultrasound, which are not routinely available in dental practice, or by using conventional CBCT, but at a significantly higher radiation dose [9,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%